TRANSFORMATION OF INTERACTIVE LEARNING MEDIA IN THE PERSPECTIVE OF EDUCATIONAL INNOVATION AND INTELLECTUAL PROPERTY RIGHTS (IPR) PROTECTION - Ayu Watawalaini; Ermis Suryana; Kurratul 'Aini (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
The transformation of education in the digital era demands innovation in the use of learning media that are more interactive, creative, and adaptive to technological developments. Learning media no longer functions merely as a supporting tool, but also as an essential instrument in improving the effectiveness and quality of the teaching and learning process. This study aims to examine the transformation of interactive learning media from the perspective of educational innovation and the importance of Intellectual Property Rights (IPR) protection for innovative works in the field of education. The method used in this research is a qualitative approach through library research by reviewing various relevant scientific sources. The results of the study indicate that interactive learning media are capable of increasing students’ motivation, creativity, and participation in the learning process. In addition, Intellectual Property Rights protection is an important aspect in maintaining the originality and legality of educational media products developed by educators and educational developers. Therefore, the transformation of interactive learning media and the protection of Intellectual Property Rights are closely interconnected in supporting sustainable educational innovation in the digital era.